Remote Display Solutions for Mobile Cloud Computing. - Simoens, Pieter; De Turck, Filip; Dhoedt, Bart; Demeester, Piet (Computer (00189162), 2011)
Proposed optimization techniques address the major challenges that varying wireless channel conditions, short battery lifetime, and interaction latency pose for the remote display of cloud applications on mobile devices.